2016
DOI: 10.1002/bem.21999
|View full text |Cite
|
Sign up to set email alerts
|

Microscale temperature and SAR measurements in cell monolayer models exposed to millimeter waves

Abstract: Due to shallow penetration of millimeter waves (MMW) and convection in liquid medium surrounding cells, the problem of accurate assessment of local MMW heating in in vitro experiments remains unsolved. Conventional dosimetric MMW techniques, such as infrared imaging or fiber optic (FO) sensors, face several inherent limits. Here we propose a methodology for accurate local temperature measurement and subsequent specific absorption rate (SAR) retrieval using microscale thermocouples (TC). SAR was retrieved by fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…The effect of a cell monolayer was numerically investigated in detail at 42 and 58.4 GHz for identical exposure conditions in Alekseev et al [] and Zhadobov et al []. They showed that the presence of a 10‐µm‐thick monolayer resulted in a 1% reduction of the total power absorbed in the sample and only slightly impacted the SAR distribution in the culture medium.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The effect of a cell monolayer was numerically investigated in detail at 42 and 58.4 GHz for identical exposure conditions in Alekseev et al [] and Zhadobov et al []. They showed that the presence of a 10‐µm‐thick monolayer resulted in a 1% reduction of the total power absorbed in the sample and only slightly impacted the SAR distribution in the culture medium.…”
Section: Resultsmentioning
confidence: 99%
“…To experimentally validate the numerical results, the following temperature‐based approach was used to determine SAR [Zhadobov et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations